IMPLEMENTASI PERATURAN DAERAH PROVINSI RIAU NOMOR 6 TAHUN 2012 TENTANG TANGGUNG JAWAB SOSIAL PERUSAHAAN DI PROVINSI RIAU (STUDI PEMBERDAYAAN MASYARAKAT DI SEKITAR PT. TAMORA AGRO LESTARI DESA SEROSAH KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI) - Made Devi Wedayanti (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
This research aims to know the Implementation of the regional province of Riau Regulation number 6 in 2012 about the social responsibility of companies in Riau Province (study of community empowerment Around PT. Agro Lestari Tamora village of Serosah sub-district of Hulu Kuantan District of Kuantan Singingi). Assessment indicators used include communication, resources and karakeristik problems. The research method used qualitative methods. This research can be categorized as descriptive research . prioritize list of interviews as a means of data collection and the data collected with this tool then made a major raw material for analyzing the empirical conditions of obyektifitas of the existence of objective research on the location thoroughly. As for the location of this research in the PT. Tamora Agro Lestari village of Serosah sub-district of Hulu Kuantan District of Kuantan Singingi with Key informants 1 person Secretary of social and Employment Office District of Kuantan Singingi and 9 people informant is Commission B the House of representatives of the regional province of Riau, Forum TJSP Province Riau, the Riau Malay custom, the House of representatives Commission III area of Kuantan Singingi, Kuantan Upstream Head , The Village Chief, Serosah, Publicist PT Agro Lestari Tamora Serosah, Chairman Of The Youth Village, Serosah Village Community. Types and techniques of collecting primary data gathered with interview techniques as well as secondary data collected through the documents, books, and records the nature of the documentation. While the data analysis technique used is to use the tools of triangulation. Based on this analysis techniques researchers assess and conclude that the Implementation of the regional province of Riau Regulation number 6 in 2012 about the social responsibility of companies in Riau Province (study of community empowerment Around PT. Agro Lestari Tamora village of Serosah sub-district of Hulu Kuantan District of Kuantan Singingi) are not fulfilled. The recommendations need to be considered especially with respect to the making of the regulations the Governor about procedures for the implementation of corporate social responsibility.